Theoretical Assumptions and Guidelines for the Elaboration of a Framework for Numeracy Assessment of Adult Students in Brasil - Maria da Conceição Ferreira Reis Fonseca; Maria Laura Magalhães Gomes; Maria da Penha Lopes (Universidad Autónoma de Madrid, 2018)
Considering the mobilization of mathematical knowledge and skills by adults responding to reading and writing demands in present Brazilian society, this article discusses the theoretical assumptions and guidelines for the elaboration of a framework for numeracy assessment of adult students in Brasil Alfabetizado Program. The choice of mathematical skills related to Numbers and Operations for assessment in such an initial acquisition process of reading and writing skills is based on Numeracy Studies and on results of large-scale comparative assessment of adult literacy like INAF (National Index of Functional Alphabetism). This article discusses both the conceptual framework for the assessment and the guidelines for the production of the test items to be responded by adults before and after training in Brasil Alfabetizado Program. The results of a Pilot Study conducted in 2005 are briefly commented as well.